Histological –Physiological Study of Thyroid Gland in White Male Rats Processing with Aluminum Chloride and Treated with Oil of Nigella sativa (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2021)
The study included two groups,  it has been designed as two experiments , in the first experiment,24 rats have divided into four subgroups  , the first subgroup received the distal water which considering the control group and the  other three subgroups have given a different aluminum chloride concentrations (80, 160, 240 mg/kg/day) for 45 days . In the second experiment 24 rats divided into four subgroups  ,the first one received a 1 ml/kg concentration of  Nigella Sativa oil, which considered as a negative control group while the rest of the subgroups received the same previous concentrations of aluminum chloride in addition to 1ml/ kg concentrations of Nigella sativa oil .The study showed a significant reduction(p